Leading dynamic information literacy programs : best practices and stories from instruction coordinators - Behler, Anne C. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Leading Dynamic Information Literacy Programs delves into the library instruction coordinator's work. Each chapter is written by practicing coordinators, who share their experiences leading information literacy programs that are nimble, responsive, and supportive of student learning. The volume discusses the work of instruction coordinators within 5 thematic areas: Claiming our Space within higher education and our institutions; Moving and Growing together; Curriculum Development; Meaningful Assessment; and Leading Change. Readers will gain insight from their colleagues' advice for situating information literacy within the higher education institution, developing meaningful curricula, and using assessment in productive ways. Many of the stories represent a departure from traditional models of library instruction. In addition, this book is sure to spark inspiration for innovative approaches to program leadership and development, including strategies for developing communities of practice. From leadership skills and techniques, methods for cultivating shared values, pedagogical approaches, team building, assessment strategies--and everything in between--the aspiring or practicing instruction coordinator has much to gain from reading this work"--
Part I. Claiming our space: library instruction in the landscape of higher education -- Navigating a shifting landscape: information literacy in higher education / Clarence Maybee -- Situating information literacy within the institution: building a dynamic program / Mary MacDonald -- Part II. Moving and growing together -- Program foundations: establishing values, boundaries, and priorities / Rebecca Miller Waltz -- From individual to community: building a community of practice around teaching / Rachel W. Gammons, Yelena Luckert, Anastasia Armendariz, Lindsay Inge Carpenter -- Part III. Curriculum development -- Instruction by design: embedding the library into curriculum design / Rachel I. Wightman -- The right tools for the job: integrating a variety of instructional modes into an information literacy program / Dani Brecher Cook -- Part IV. Meaningful assessment -- Improving information literacy instruction through programmatic student learning assessment / Maoria J. Kirker, Ashley Blinstrub -- Part V. Leading change -- That's not the way we've always done it: coordinating research instruction with innovation, teamwork, assessment, and collaboration / Emily Z. Brown, Susan Souza-Mort -- Time for a reboot! Making space for instruction program development / Anne C. Behler.
OCLC-licensed vendor bibliographic record.
Keywords: Instruction librarians -- Professional relationships -- United States; Information literacy -- Study and teaching (Higher) -- United States; Information literacy -- Study and teaching (Higher) -- United States -- Evaluation; Library orientation for college students -- United States; Academic libraries -- Relations with faculty and curriculum -- United States; COMPUTERS / Computer Literacy; LANGUAGE ARTS & DISCIPLINES / Literacy